Model Of Sugar Industrial Waste Management Based On Cleaner Production (Case Study: Sei Semayang Plantation and Sugar Mill) - Siti Mardiana; Retno Widhiastuti; Sumono Sumono; Luqman Erningpraja (Budapest International Research and Critics University, 2020)
Controlling the amount and level of sugar industry waste must be done carefully, ranging from sugar cane harvesting in the field to the processing of cane into sugar mill. The aim of this research is constructing model and getting strategy and policy of sugar industry waste management based on clean production using dynamic system. This research was conducted at Sei Semayang plantation and sugar mill, PTPN II, North Sumatera in January until July 2013.Dynamic model system of waste management based on clean production was analyzed using Powersim program, license by sofware house Powersimtm, USA. The research shows Dynamic model of sugar industry waste management can be done by combining environmental subsystem model and socio-economical subsystem. The scenario and policy of sugar industry waste management based on clean production results in waste minimilization, production process efficiency and increase of agricultural contribution, that it increases the surrounding community’s income and involvement, and the company’s income.